Influence of Feeding on Indigenous Commercial Poultry Production in Mandera County, Kenya - Mohamud, Mohamed; Mutunga, Stephen Laititi; Koome, Martin (International Journal of Professional Practice, 2023)
Indigenous poultry thrive in arid and semi-arid lands since they require less care, are hardy, and can scavenge on free range. However, supplementation of poultry feeds with commercial rations has been shown to give better results. A number of obstacles in feeding indigenous chicken restrict their production, especially in arid lands. The objective of this study was to evaluate the influence of supplementary feeding on commercial indigenous poultry production in Mandera County, Kenya. Descriptive study design was used. The study population was 3,971 poultry keeping households in Mandera County, from which 363 respondents were purposively selected. Purposive sampling technique ensured that poultry keepers with over 100 indigenous chickens for commercial purposes and those practicing supplementary feeding were selected. Questionnaires and interview schedules were used to collect data. Focus group discussions were used for qualitative data and triangulation of results. Reliability of instruments as ascertained by Cronbach alpha value. The findings revealed that feeding had a positive and significant effect on poultry production (β=1.108, p=0.000). Person’s correlation coefficient on influence of poultry feeding on indigenous commercial chicken production was positive, high (r=584**) and significant. The study concluded that poultry feeding experienced challenges. Further, due to lack of technical advisory services, majority of commercial poultry producers result to traditional poultry feeding practices which stagnated their production. The study recommends county governments to recruit additional livestock extension specialists, and to create an enabling environment for businessmen to invest in commercial poultry feeds production. The study proposes further research on factors that affect supplementary feeding, their effects on the commercialization of indigenous poultry production.